Histogenesis of Prenatal Liver of Goat (Capra hircus) - Singh, Gajendra; Farooqui, M. M.; Prakash, Ajay; Pathak, Archana; Kumar, Prabhakar (Indian Journal of Veterinary Anatomy, 2013)
For this study 18 goat embryos/foetii of either sex ranging from 17 days old to full term were collected from the aborted/clinical cases arrived at hospital of the college. The specimens were divided in to three groups. The primordium of the liver appeared as irregular solid strand of hepatocytes separated by irregular and broad blood spaces at 17 days of gestation. It was composed of hepatocytes, haemopoietic cells and nucleated RBCs. Small capillary spaces in between the hepatic cords (future hepatic sinusoids) were noticed at 20 days of gestation. Radial arrangement of hepatocytes, lobule formation and portal triad were first observed at some places at 49 days of gestation.